Desain Pembelajaran Peningkatan Literasi Numerasi dan Karakter Berpikir Kritis Siswa SD Berbasis Etnomatematika - Susanto, Nabilla Calista Putri; Hartati, Sulis Janu; Setiawan, Windi (Universitas Nahdlatul Ulama Pasuruan, 2022)
This study aims to produce a learning design to increase numeracy literacy and critical thinking character of elementary school students based on ethnomathematics using Polya's problem-solving steps. This type of research is library research. The results showed that Polya's problem-solving steps can be used to design learning syntax as follows. Polya's first step is to understand the problem of producing a learning design menu, let's get to know culture, learn to get flat, and learn numeracy through films or videos from the MK Modul NusantaraMBKM Dr Soetomo University. The second step is polya learning planning to produce a learning design menu for identifying flat shapes based on the questions in learning numeracy with number content, geometry & measurement, algebra, and data & uncertainty. The third step is to implement the lesson plan, produce a learning design menu, let's develop alternative answers. The fourth step is to reflect on learning to produce a learning design menu, let's reflect. Increasing numeracy literacy and critical thinking character can be built on the first, second, third and fourth steps of solving Polya's problems.